2015
DOI: 10.1590/2317-1782/20152014167
|View full text |Cite
|
Sign up to set email alerts
|

Auditory-perceptual evaluation of the degree of vocal deviation: correlation between the Visual Analogue Scale and Numerical Scale

Abstract: The visual analog scale and numerical scale showed a strong correlation, being observed the greater intra- and inter-rater agreement in visual analog scale. Numerical cutoff values for visual analog scale were found. This correlation enables the comparison between the results found in the evaluation of the overall degree of vocal deviation by both scales, which are widely used in research and in the clinical speech therapy routine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0
4

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 19 publications
2
20
0
4
Order By: Relevance
“…In this study, a strong correlation was observed between the VAS and the NS, and the VAS presented higher inter-rater reliability. The results agreed with the results of a study by Martins et al, 26 in which they correlated VAS and NS in auditory-perceptual evaluations, and pointed out that the VAS was more sensitive to small marking differences than the NS. The Likert scale is a form of NS, and it typically has five to seven response levels.…”
Section: Discussionsupporting
confidence: 91%
“…In this study, a strong correlation was observed between the VAS and the NS, and the VAS presented higher inter-rater reliability. The results agreed with the results of a study by Martins et al, 26 in which they correlated VAS and NS in auditory-perceptual evaluations, and pointed out that the VAS was more sensitive to small marking differences than the NS. The Likert scale is a form of NS, and it typically has five to seven response levels.…”
Section: Discussionsupporting
confidence: 91%
“…In this group of athletes, all MPT (vowels, fricatives, [ė] and vowel average) were below normality. These results suggest transglottic air leakage and IPFA (Cielo et al, 2015, Cielo, Frigo, Christmann, 2013, Martins, Couto, Gama, 2015, Pinho, 2003 (Table 1) and are in agreement with research in which MPT /a/, /i/ and /u/ were significantly decreased in men.…”
Section: Discussionsupporting
confidence: 89%
“…The modal SPL was obtained through the emission of the vowel /a:/, with sound pressure meter (Icel, DL-4200), positioned 90º in front of the subject's mouth and 30 cm away (Beber, Cielo, 2011, Behlau et al, 2013, Cielo et al, 2015, Cielo, Frigo, Christmann, 2013, Martins, Couto, Gama, 2015. The normality value of modal SPL for men was 64 dB (Behlau et al, 2013).…”
Section: Methodsmentioning
confidence: 99%
“…The assignments were as follows: 0 as no pain, 1 to 2 as mild pain, 3 to 6 as moderate pain, and ≥ 7 as severe pain. [20] The assessment of dizziness was represented as yes or no.…”
Section: Methodsmentioning
confidence: 99%